Kombu-feed: a nutritive & prophylactic alternative for fish production / Ruhil Hayati Hamdan ... [et al.] - Hamdan, Ruhil Hayati; Tan, Li Peng; Mohamed, Nora Faten Afifah; Mat Zin, Ain Auzureen; Samsuddin, Ahmad Syazwan (2021)
Out of all the commercially cultured freshwater species, catfish accounts for 45.19% which is the highest of the freshwater aquaculture production with African catfish becoming one of the topmost cultured freshwater fish. The need for improved feed efficiency, growth performance and disease resistance of cultured organism become substantial as the costs of production are likely to be reduced in a commercial setting. One of the options is feed additives which have been available for years to improve the growth performance of fish. Therefore, this study was conducted to investigate the potential of kombucha tea used as a feed supplement for African catfish, Clarias gariepinus, specifically to increase weight gain, specific growth rate and feed conversion ratio. Treatment diet containing kombucha tea culture was prepared and given to the treatment group while the control group was given diet without any kombucha culture twice daily for thirty-five days. The results showed a significant increase in growth performance where the weight gain, specific growth rate and feed conversion efficacy increased by two-folds in the treatment group compared to the control group. This study proved that there was evidence of growth promoter property of kombucha tea in terms of weight gain, specific growth rate and feed conversion efficacy in African catfish.